PEMBERIAN HUKUMAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Muhammad Fauzi (AL - IBRAH, 2016)
Education is a maturing process of learning a very complex learners systematically through a curriculum that is applied in the educational unit that is useful to explore the potential of students from various facets of the life of society, nation and state. To realize these goals much needed discipline and sense of responsibility in the learning process. Consistency discipline and sense of responsibility in the learning process, then the required method or preventive measures, one such method is the provision of a penalty or punishment in educational units aimed accompany the learning process in order to achieve educational goals that had been expected. We need to know the substance rather than reward and punishment will not be separated in the educational process as well as the essence of good and bad are both always go hand in hand at the wheel of life. Therefore, punishment in the educational process must be in accordance with Islamic education that directs learners to always berakhlaqul karimah able to distinguish between good and bad behavior in daily life both in the school environment and society in general.